CsrA-FliW interaction governs flagellin homeostasis and a checkpoint on flagellar morphogenesis in Bacillus subtilis - Mukherjee, Sampriti (2011)
CsrA is a widely distributed RNA binding protein that regulates translation initiation and/or mRNA stability of target transcripts. CsrA activity is antagonized by sRNA(s) containing multiple CsrA binding sites in several Gram-negative bacterial species. Here we discover FliW, the first protein antagonist of CsrA activity that constitutes a partner switching mechanism to control flagellin synthesis in the Gram-positive organism Bacillus subtilis. Following the flagellar assembly checkpoint of hook completion, secretion of flagellin (Hag) releases FliW protein from a FliW-Hag complex. FliW then binds to CsrA and relieves CsrA-mediated translational repression of hag for flagellin synthesis concurrent with filament assembly. Thus, flagellin homeostatically restricts its own translation. Homeostatic autoregulation may be a general mechanism to precisely control structural subunits required at specific times and in finite amounts such as those involved in the assembly of flagella, type III secretion machines, and pili. Finally, phylogenetic analysis suggests that CsrA, a highly pleiotropic virulence regulator in many bacterial pathogens, had an ancestral role in flagellar assembly and evolved to co-regulate various cellular processes with motility.